4(0.5x-3)=-0.25(12-8x)

Simple and best practice solution for 4(0.5x-3)=-0.25(12-8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(0.5x-3)=-0.25(12-8x) equation:



4(0.5x-3)=-0.25(12-8x)
We move all terms to the left:
4(0.5x-3)-(-0.25(12-8x))=0
We add all the numbers together, and all the variables
4(0.5x-3)-(-0.25(-8x+12))=0
We multiply parentheses
0x-(-0.25(-8x+12))-12=0
We calculate terms in parentheses: -(-0.25(-8x+12)), so:
-0.25(-8x+12)
We multiply parentheses
2x-3
Back to the equation:
-(2x-3)
We add all the numbers together, and all the variables
x-(2x-3)-12=0
We get rid of parentheses
x-2x+3-12=0
We add all the numbers together, and all the variables
-1x-9=0
We move all terms containing x to the left, all other terms to the right
-x=9
x=9/-1
x=-9

See similar equations:

| 7y+4+4y+8=78 | | -7/5+1/3v=-1/2 | | 2/3e=1/18 | | 14x+4x-8=14 | | 2x+5=34+3x | | (1/5)(25x+15)-3=2x+9+3 | | ‐4(‐3x+1)−7x=5x−4 | | z-2÷1/4=2 | | 2x-(5x-7)=22+x | | 2-4n=-12+3n | | 2d-2,7=1,76 | | w/2+ 3.16=6.16 | | −2(2x−5)+5x=14 | | 17.79=3g+3.81 | | 8v-19=15 | | 2(x+1)-(x-1)=-7 | | 24x−8= | | 24x−8=8(3x−1 | | u+13.1/2=-1.1 | | 3x+24=57 | | 14x-35=10x+1 | | 9=13+r | | 9-4k=17 | | Y=-2x2+8x-8 | | 23-6t=83 | | 3x+226=7(x-6 | | 3x+336=7(x-6) | | 22=  b2−22b​ | | 9(t-2)=4(t+-15) | | 2/3(y-7)=-4 | | v=(124)(28)(56) | | v=(124)(28)(56)/3 |

Equations solver categories